(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the relationship of nutritional status with the level of physical activity of institutionalized and non-institutionalized elderly. Method: This is a cross-sectional study. The sample size is 245 institutionalized and 105 socially active elderlies, non- institutionalized, assisted in a Family Healt Strategy, from Rio Grande do Sul. The International Physical Activity Questionnaire, short version, and a structured questionnaire with variables about name, age, gender, current weight, and height was used. Nutritional status was classified according to the Pan American Health Organization (2002). Epi Info 7.2 software was used to analyze the results that were considered significant at a maximum significance level of 5%. Results: The obesity the level of active physical activity, very active and the age group from 60 to 69 years old have become significantly for the non-instituonalizes elderly and for underweight sedentary physical activity level and age of 80 years and over to institutionalized elderly (p≤0.01). Low weight was significantly associated with the elderlies with sedentary level of physical activity and obesity at the active and very active level (p≤0.01) Conclusion: The most non-institutionalized elderly were obese, active physical activity level or very active and were 60 to 69 years old, while institutionalized elderly were underweight or eutrophy or overweight, sedentary and aged 80 or over. Obese elderly people practiced more physical activity compared to those classified as underweight.